The Slow Down Program: A mixed methods pilot study of a mindfulness-based stress management and nutrition education program for mothers. (June 2018) - Kennedy, Lauren E.; Misyak, Sarah; Hosig, Kathy; Duffey, Kiyah J.; Ju, Young; Serrano, Elena
Highlights: Stress is a contributor to a broad range of adverse health outcomes and unhealthy eating behaviors, particularly in mothers. The effectiveness of mindfulness-based programs on stress is well established, but less is known about their effect on eating behaviors. The Slow Down Program is a mindfulness-based stress management and nutrition education program designed for mothers. Mindfulness-based stress management may be an effective approach to managing stress and improving unhealthy eating behaviors. Abstract: Objective: Stress levels have been associated with a broad range of adverse health outcomes, particularly for mothers and subsequently, their children. Mindfulness-based stress management is a tool that has effectively been utilized in several disciplines and has potential applications to eating behaviors. This paper describes the effects of an exploratory mindfulness-based stress management and nutrition education program, the Slow Down Program, on mothers' perceived stress, eating behavior, and self-efficacy. Design & setting: This study used a mixed methods quasi-experimental design. Nineteen mothers with young children (five or younger) participated in the study. The SDP consisted of four consecutive weekly 1.5 h sessions focused on experiential learning and facilitated discussion. Main outcome measures: Quantitative data were collected pre- and post-intervention and included: the Perceived Stress Scale; Mindfulness Self-Efficacy Scale; and the Three-Factor Eating Questionnaire Revised-18. Qualitative data included a focus group post-intervention and an individual interview 4–6 weeks post-intervention. Results: The SDP showed significant improvements in participants' perceived stress (p = .04), uncontrolled eating (p < 0.01), cognitive restraint (p < 0.01), and mindfulness self-efficacy (p < 0.01). Qualitatively, participants also reported changes in self-efficacy and eating behaviors – specifically improvements in mindful eating, and sensory and satiety awareness. Conclusions: The results of this pilot study demonstrate that nutrition programs incorporated with mindfulness strategies may offer positive, short-term impacts on stress reduction and eating behaviors. Additional studies are warranted across a variety of populations with more rigorous study designs to assess long-term effects.